2010
DOI: 10.1007/s12199-009-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heart rate variability and cardiac arrhythmias in polluted and clean air episodes in healthy individuals

Abstract: Objective Pathophysiological mechanisms and pathways linking cardiovascular mortality and morbidity with air pollution were recently hypothesized. The present study evaluated association between air pollution and changes in heart rate variability as a marker of cardiac autonomic function in healthy individuals, and also determined the frequency of cardiac arrhythmias and QT interval changes on polluted compared to unpolluted days. Methods Continuous Holter electrocardiography (ECG) monitoring was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Indeed, other reports note increased HRV as an indicator of heightened risk. For example, increased RMSSD has been shown to be associated with elevated risk of air pollution-induced arrhythmia (Davoodi et al, 2010) and increases in HRV have been demonstrated preceding post-operative atrial fibrillation (Amar et al, 2003). Additionally, increases in vagal tone have been associated with adverse cardiovascular events in type II diabetics (Eguchi et al, 2010), and linked with increased mortality in heart failure patients and the elderly (de Bruyne et al, 1999; Stein et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other reports note increased HRV as an indicator of heightened risk. For example, increased RMSSD has been shown to be associated with elevated risk of air pollution-induced arrhythmia (Davoodi et al, 2010) and increases in HRV have been demonstrated preceding post-operative atrial fibrillation (Amar et al, 2003). Additionally, increases in vagal tone have been associated with adverse cardiovascular events in type II diabetics (Eguchi et al, 2010), and linked with increased mortality in heart failure patients and the elderly (de Bruyne et al, 1999; Stein et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…). The occurrence of non-sustained supraventricular tachycardia, as a marker of cardiac dysfunction, was recorded in almost 43% of the participants during the polluted air conditions, whereas this arrhythmia was not reported during the non-polluted conditions (p = 0.001) [65]. A major aspect in the development of early-life atherosclerosis is the relationship of air pollution with endothelial dysfunction and pro-coagulation effect.…”
Section: Kingdom Of Saudi Arabiamentioning
confidence: 89%
“…Controlling or reducing anthropogenic sources of the outdoor air pollution would help clean the air we breathe, as well as minimize its health burden in the whole population. 120.48 [66] vehicle emissions, temperature inversion in cold seasons [60] potential impact of PM on platelet activation and atherosclerosis [64] changes in the heart rate variability as a marker of cardiac autonomic dysfunction in the polluted air conditions [65] on average, 1 367 extra total deaths and 2 580 extra cases admitted to hospitals due to CVD annually were attributable to an increase by 10 μg/m 1072-80.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In whole atmosphere studies, cardiovascular effects were not clearly associated with air pollution mixture exposures to high and low traffic environments for adults with regard to heart rate, blood pressure, and blood glucose parameters (Kubesch et al, 2014;Larsson et al, 2007;Laumbach et al, 2010). Similarly, cardiovascular effects were not associated with air pollution mixtures examined as high and low air pollution days in Atlanta GA (Peel et al, 2010), or Tehran, Iran (Davoodi et al, 2010). Some of the inconsistency observed in whole atmosphere studies could be due to the differences in pollutant composition (mainly O 3 and CO versus mainly PM and NO 2 ).…”
Section: Air Pollution Mixturesmentioning
confidence: 94%